Analysis of Pap Smear Database in a Community Hospital - Sharma, R; Baral, GN; Dangal, G (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: This study was done to find out age wise distribution pattern, cellular abnormality and adequacy of Pap smears. Methods: A retrospective study of 4800 Pap smears based on laboratory database was done from 2008 to 2011 at Helping Hands Community Hospital in Kathmandu, Nepal. Graphical method was used for normality test and frequency analysis was done using SPSS 16. Results: Out of 4794 analysable data 4.21% had abnormal cytology, all high-grade lesions were in 51-65 age group and 0.06% were detected as carcinoma. Age group of 30-65 years covers four-fifth of the samples (3811, 79.4%) and 85.6% of abnormal cytology (173 out of 202) with maximum samples (3313, 69%) at 30-50 years and 55.44% of abnormal cytology. Only 5.4% of samples categorized as inadequate by Bethesda reporting system. Age wise distribution of samples produced near normal Gaussian curve. Conclusions: Pap samples were normally distributed by age. Test requisition forms lack adequate clinical information. Even the inadequately sampled Pap smears were satisfactory for evaluation. DOI: http://dx.doi.org/10.3126/njog.v9i1.11182 NJOG 2014 Jan-Jun; 2(1):21-25